1995
DOI: 10.1164/ajrccm/151.4.1075
|View full text |Cite
|
Sign up to set email alerts
|

Early Pulmonary Inflammation in Infants with Cystic Fibrosis

Abstract: The mechanisms underlying the initiation of lung disease and early respiratory morbidity in cystic fibrosis (CF) are poorly understood. By identifying infants with CF through a statewide neonatal screening program, we investigated whether airway inflammation was present in these infants, with the goal of furthering our understanding of the early events in this lung disease. Bronchoalveolar lavage fluid (BALF) from 16 infants with CF (mean age, 6 mo) and 11 disease control infants (mean age, 12 mo) was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
534
3
11

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 658 publications
(575 citation statements)
references
References 0 publications
21
534
3
11
Order By: Relevance
“…Studies have shown that patients with CF have an inherent pro-inflammatory environment in the lungs and an excessive response to bacterial infection. [2][3][4][5][6][7][8][9][10][11] This study continues to lay the foundation towards characterizing AAV-based IL-10 delivery as a viable therapeutic for CF lung disease. In future studies, it will be important to further define the molecular pathways of AAV-IL10-based immunomodulation and persistence, as well as physical barriers to vector entry and expression.…”
Section: Il-mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that patients with CF have an inherent pro-inflammatory environment in the lungs and an excessive response to bacterial infection. [2][3][4][5][6][7][8][9][10][11] This study continues to lay the foundation towards characterizing AAV-based IL-10 delivery as a viable therapeutic for CF lung disease. In future studies, it will be important to further define the molecular pathways of AAV-IL10-based immunomodulation and persistence, as well as physical barriers to vector entry and expression.…”
Section: Il-mentioning
confidence: 99%
“…The role of inflammation in the pathogenesis of CF has IL-10 gene transfer attenuates pseudomonas pneumonia SM Buff et al been controversial, but the majority of current evidence supports the hypothesis that airway inflammation in CF is exaggerated and pathological. [2][3][4][5][6][7][8][9][10][11] Although antiinflammatory treatments for CF airway disease have been associated with modest improvements in lung health, none have achieved a high rate of success, and several carry the risk of significant side effects. Therefore, the development of safer and more effective antiinflammatory therapies continues to be essential.…”
Section: Il-mentioning
confidence: 99%
See 1 more Smart Citation
“…Children with CF have structurally normal lungs at human CFTR expression in both adult rabbit 3 and pribirth, but evidence of inflammation can be found very mate models, 4 as well as in cultured CF bronchial epiearly in life. 1 It is therefore likely that the optimal time thelial cells. 5 While wild-type AAV persists by sitefor transduction of functional CFTR into the pulmonary specific integration into human chromosome 19, 6,7 AAV epithelium of a CF patient is in the neonatal period prior vector DNA persists predominantly in an episomal to the onset of pulmonary inflammation and damage.…”
Section: Introduction Expanding Lung Cystic Fibrosis (Cf) Is a Multimentioning
confidence: 99%
“…2 Since the cloning of the gene for CF in 1989, 3 there has been much interest in the development of gene therapy. This has now reached the stage of clinical trials in adults 4 but these patients already have established disease.…”
Section: Introductionmentioning
confidence: 99%